Power, Resources, and Justice: Evaluating International Courts in Settling Transboundary Natural Resource Conflicts - Wijayanti, Aprilia; Fikri, Wildan Azkal; Purnomo, Didik; Kusuma, Bagus Hendradi; Sumardiana, Benny (Indonesian Journal of Environmental Law and Sustainable Development, 2024)
Transboundary natural resource disputes—ranging from water rights and mineral extraction to fishing zones—pose complex challenges to the international legal system, often threatening regional stability, economic development, and diplomatic relations. This paper evaluates the effectiveness of international courts in resolving such disputes between sovereign states, focusing on how legal principles, judicial authority, and enforcement mechanisms interact to manage conflicts over shared resources. By examining case studies from the International Court of Justice (ICJ), arbitral tribunals, and other relevant judicial bodies, the study assesses both successes and limitations in achieving equitable and sustainable outcomes. The analysis highlights key factors that influence the effectiveness of international adjudication, including the clarity of legal norms, the willingness of states to submit to jurisdiction, the availability of evidence, and the political and economic stakes involved. While international courts have demonstrated the ability to provide neutral platforms, clarify legal obligations, and shape normative expectations, enforcement challenges and state resistance often limit their practical impact. Moreover, complex scientific, environmental, and technical issues can complicate judicial decision-making, particularly in disputes over shared watercourses, fisheries, and transboundary natural resources. Despite these challenges, the paper argues that international courts play a critical role in promoting accountability, preventing escalation, and guiding cooperative resource management. The study concludes that while courts cannot guarantee compliance or resolve all conflicts, their jurisprudence significantly contributes to the development of international law, offers frameworks for negotiation, and encourages peaceful, rules-based resolution of disputes. Strengthening legal frameworks, promoting regional cooperation, and enhancing compliance mechanisms are essential to maximize the impact of judicial intervention in resource conflicts.